Kualitas Hidup Pekerja Dinas Pendidikan Kaitannya dengan Body Mass Index Terhadap Cardiorespiratory dan Denyut Nadi Istirahat - Atep Sugri Hilman (Universitas Pendidikan Indonesia, 2020)
The purpose of this study was to determine the relationship between blood pressure, respiratory rate and resting pulse on body mass index in relation to the quality of life of structural workers. Samples were taken as many as 89 workers in the Bandung City Education Office, using simple random sampling technique. Data collection uses a questionnaire (WHOQOL-BREF Questionnaire) to measure quality of life, Body Mass Index is obtained from the results of a discretionary measurement of height and weight using the formula BW (kg) / TB (m2), blood pressure is measured using a Blood Pressure Monitor, while the frequency of breaths is measured by calculating the rate of breath that occurs when the subject inspires and expires air which is counted for one minute, and pulse is measured using a Pulse Oximeter. Statistical calculations using SPSS with Pearson partial correlation analytical statistics. Conclusion: First, there is a positive and significant relationship between BMI and quality of life on blood pressure with an R square value of 0.145 or 14.5% for systolic blood pressure and 0.259 or 25.9% for diastolic blood pressure. Second, there is no relationship between BMI and quality of life on resting pulse with an R square value of 0.027 or 2.7%. Third, there is no relationship between BMI and quality of life on respiratory rate with an R square value of 0.041 or 4.1%.